2014
DOI: 10.1152/ajprenal.00600.2013
|View full text |Cite
|
Sign up to set email alerts
|

LIM homeobox transcription factor 1B expression affects renal interstitial fibrosis and apoptosis in unilateral ureteral obstructed rats

Abstract: homeobox transcription factor 1B expression affects renal interstitial fibrosis and apoptosis in unilateral ureteral obstructed rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Masson's trichrome is a three-color staining protocol used in histology, which produces red fibers, blue collagen, pink cytoplasm, and dark brown nuclei [ 32 ]. In the LFD control group, kidney tubular endothelial cells presented fullness of pink cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Masson's trichrome is a three-color staining protocol used in histology, which produces red fibers, blue collagen, pink cytoplasm, and dark brown nuclei [ 32 ]. In the LFD control group, kidney tubular endothelial cells presented fullness of pink cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…Renal interstitial fibrosis (RIF) was scored from 0 to 3 as follows: 0 = absent ( n 0 ), 1 = less than 25% of the area ( n 1 ), 2 = 25–50% of the area ( n 2 ), and 3 = more than 50% of the area ( n 3 ). The RIF index was calculated according to the following equation: RIF index = (0 × n 0 + 1 × n 1 + 2 × n 2 + 3 × n 3 )/( n 0 + n 1 + n 2 + n 3 ) × 100% [ 32 ]. All sections were scanned using an Olympus BX51 microscope (Olympus, Tokyo, Japan) and analyzed using Image J software (National Institutes of Health, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence suggested that LMX1B is widely expressed in types of human tissues, including testis, thyroid, pancreatic islets, ocular, and skeletal muscle [15,28,29]. LMX1B has been shown associated with cell proliferation, migration, apoptosis, and inflammatory cytokine production [30][31][32]. As a transcription factor, LMX1B could regulate multiple pathways and cell physiologies via mediating associated target genes [11].…”
Section: Discussionmentioning
confidence: 99%
“…The stromal cellspecific functions of these have not yet been reported. However, due to the presence of studies that link fibrosis with some homeobox genes, their role in this condition should be investigated in detail (Wandzioch, 2004;Zhou, 2014;Gong, 2017).…”
Section: Discussionmentioning
confidence: 99%